PENGEMBANGAN MEDIA PENDIDIKAN UNTUK INOVASI PEMBELAJARAN DI PESANTREN - Munif Shaleh; Abd. Aziz (Universitas Yudharta Pasuruan, 2020)
The increasingly dynamic development of information technology has implications for the world of education, especially learning activities. One of them by using media for helping the easy learning process that is very receive as benefit. Learning media can enhance student learning help to create joyful learning. But is not all learning media that can be applied in every learning environments, because learning media has advantages and disadvantages in several aspect. For the example is classical learning methods such as wetonan and bandongan become a characteristic teaching and learning activities in pesantren. Because of that, require a efforts to develop educational media suitably with the learning and the needs of students. Learning media development procedures iclude are potential and problems, data collection, product design, design validation, revision, small-field trials, revision, large-field trials, revision, massive production